2011
DOI: 10.1111/j.1442-2018.2011.00596.x
|View full text |Cite
|
Sign up to set email alerts
|

Turnover intention among Italian nurses: The moderating roles of supervisor support and organizational support

Abstract: The purpose of this study was to examine the variables that are related to person-environment fit in Italian nurses, highlighting the role of supervisor support and organizational support in the relationship between nurses' perceptions of care adequacy, job satisfaction, and turnover intention. Therefore, 1240 nurses from three hospitals completed a self-administered questionnaire. The results showed that supervisor support and organizational support act differently as moderators of the care adequacy-job satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
83
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 34 publications
9
83
1
7
Order By: Relevance
“…This result was consistent with the results of previous studies (e.g. Galletta, Portoghese, Penna, Battistelli, & Saiani, 2011;Newman et al, 2012). These results showed that when health workers perceive their hospitals' support positively and with high level (M=3.41), their intention to leave their present hospital would be decreased.…”
Section: Discussionsupporting
confidence: 93%
“…This result was consistent with the results of previous studies (e.g. Galletta, Portoghese, Penna, Battistelli, & Saiani, 2011;Newman et al, 2012). These results showed that when health workers perceive their hospitals' support positively and with high level (M=3.41), their intention to leave their present hospital would be decreased.…”
Section: Discussionsupporting
confidence: 93%
“…All studies involved adult workers and used a sample size ranging from 239-1240. Only one study involved registered nurses [15]. The characteristics of samples are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies examined the work-related supervisor support, which commonly was called Perceived Supervisor Support (PSS). Examples of PSS behaviors included: recognition, encouragement, and positive feedback [15]. Two studies examined the family-related supervisor support, including behaviors such as listening and showing care for employees' work-family demands, and responding to an employee's family needs in the form of day-to-day management [16].…”
Section: Synthesis Of Literature Types Of Supervisor Support Behaviorsmentioning
confidence: 99%
“…Cette situation préoccupante est particulièrement problématique dans le secteur de la santé, notamment chez le personnel infirmier (Galletta et al, 2010). Selon Wagner (2010), le roulement des infirmiers et des infirmières est un dysfonctionnement qui affecte négativement la performance en matière de ressources humaines et, ultimement, celle de l'organisation tout entière : en effet, une réduction de l'effectif influencera négativement la qualité des soins donnés, augmentera la charge de travail de ceux et celles qui auront survécu au roulement, baissera le moral de ces rescapés et risquera d'intensifier leurs intentions de quitter suite au bris ressenti du contrat psychologique de travail.…”
Section: Résumé De L'articleunclassified